Power and linguistic meritocracy: Dialect interference and symbolic capital among Sundanese-Banten EFL learners - Fajri, Khaerul; Istifadah, Istifadah (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
The language diversity in Indonesia raises the phenomenon of language interference as occurs in Sundanese Banten students when speaking English as a global language. However, as language learning is never neutral, the process is oft-shaped by power relations and ideologies, while the result is often valued based on the linguistic meritocracy. Therefore, as related to the Sundanese Banten dialect, this study aims: (1) to identify the types of dialectal interference that occur when Sundanese-Banten EFL learners speak English, and (2) to explore the system of values that emerges from linguistic meritocracy in relation to their pronunciation, as shaped by global society views. While using a qualitative method to find and analyze the dialectical interference; the Bourdieu theory, language accent as a symbolic power through linguistic meritocracy, is also used to explore the intersection between the language pronunciation reality, the linguistic meritocracy in it, and the societal system of value. After going through a series of analyses, there are seven primary interferences that internalized into the Sundanese Banten dialect, they are Lenition, Fornition, Syncope, Apocope, Epenthesis, and Prague as several intermittent letters were found such as [ð] changed to [d], [ʤ] to [g], [v] to [f], [z] to [s], and [r]. These interferences, while linguistically common, are socially charged; they reflect how systems of linguistic value classify learners according to perceived intelligence and cultural capital. In this sense, pronunciation becomes not merely a linguistic feature but a marker of social legitimacy and symbolic capital within the ideology of linguistic meritocracy.